Psychological distress and experience of sexual and physical assault among Australian prisoners - Schneider, K.; Richters, J.; Butler, Tony; Yap, L.; Richards, A.; Grant, L.; Smith, A.; Donovan, B. (2011)
Background Prison populations are made up of individuals from disadvantaged, often abusive backgrounds, who are more likely to suffer from psychological problems than the general community. Aim This study aimed to determine associations between current psychological distress and history of having experienced sexual coercion and/or physical assault among prisoners in two Australian states (Queensland and New South Wales). Methods We conducted a random sample survey of prisoners by computer-assisted telephone interview. Prisoners were asked about forced sexual encounters in or outside prison, and physical assault in prison. Psychological distress was estimated using a dichotomised score obtained from the Kessler 6-Item Psychological Distress Scale (K6), and a logistic regression analysis was employed to investigate associations. Results A total of 2426 prisoners were interviewed of 3055 prisoners invited to participate, a response rate of 79%. We categorised 236 men (12%) and 63 women (19%) as 'severely' psychologically distressed according to the K6, and 13% of the men and 60% of the women reported that they had been sexually coerced prior to imprisonment. Physical assault in prison was common, reported by 34% of the men and 24% of the women. On multivariate analysis, prisoners were more likely to be psychologically distressed if they had ever been threatened with sexual assault in prison or physically assaulted in prison. Sexual coercion outside prison was an important associate of psychological distress among men but not among women. Conclusions As psychological distress and experiences of assault are closely statistically linked among male prisoners and both are very common among female prisoners, their screening for psychological distress should include efforts to find out about sexual and violent assaults against them both before and during imprisonment. Further, longitudinal research with prisoners is required to establish causal relationships. Copyright © 2011 John Wiley & Sons, Ltd.